Case of Takayasu syndrome in clinical practice - Syvolap, V. V.; Kurilets, L. O. (Zaporozhye Medical Journal, 2014)
Aim. Modern data about etiology, pathogenesis, clinical symptom of the Takayasu syndrome are given in the article. Materials and methods. Tomography, sonography has important role in the diagnosis of the nonspecific aortoarteritis. Treatment with medication that inhibits IL-6 receptors and B-cells is discussed. Self data are presented, clinical picture of the Takayasu syndrome in young female is described. Conclusions. Feature of the disease as multifocal stenosis of the aorta, common carotid artery, brachiocephalic artery, subclavian and axillar artery are described.